2018
DOI: 10.18388/abp.2017_2344
|View full text |Cite
|
Sign up to set email alerts
|

Role of Apolipoprotein E gene polymorphism in the risk of familial hypercholesterolemia: a case-control study

Abstract: Familial Hypercholesterolemia (FH) is characterized by elevated cholesterol; this is based on biochemical, clinical, and genetic studies and FH disease, which was documented even with limited mutations. Earlier studies were associated with Apolipoprotein E (ApoE) in variable diseases. The current study aims to investigate the genetic association between FH disease and ApoE gene (rs429358 and rs7412) in the Saudi population. This study has been carried out as a case-control and is a hospital-based study in Saud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 75 publications
0
4
1
Order By: Relevance
“…Benign APOE gene variant rs429358 was found in 16 patients, almost 20 %, of our group. In our group we did not find APOE Leu167del mutation, causing FH, observed in Italian and French populations [38][39][40][41].…”
Section: Apoe Gene Variants Rs429358 and Rs7412 Are Included By The G...contrasting
confidence: 62%
“…Benign APOE gene variant rs429358 was found in 16 patients, almost 20 %, of our group. In our group we did not find APOE Leu167del mutation, causing FH, observed in Italian and French populations [38][39][40][41].…”
Section: Apoe Gene Variants Rs429358 and Rs7412 Are Included By The G...contrasting
confidence: 62%
“…Another recent Meta-Analysis based on 27 studies with 3136 dementia and 3103 healthy controls reported that circulating cholesterol was significantly increased in APOE ε4 carriers in mixed populations [11]. The cholesterol-associated APOE ε4 allele was also reported in the Saudi- [12] White- [13][14][15][16], Afro-Caribbean- [10], and Asian- [17,18] populations. The role of APOE genetic variation on interindividual variation in the plasma cholesterol has been wellestablished, especially LDL-C in non-Hispanic White and African Black populations [19].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, our results were consistent with the previous studies in Thai population (E2 6.64–7.11 %, E3 76.35–79.56 %, E4 13.33–17.01 %) ( Wanmasae et al, 2017 , Srirojnopkun et al, 2018 ). Whereas, the APOE4 allele from these findings was higher than Saudi (5.5–11.5 %) ( Almigbal et al 2018 ), Han Chinese (7.5 %) ( Han et al 2016 ), Taiwanese (7.5 %) ( Vasunilashorn et al 2013 ), Korean (9 %) ( Shin et al 2014 ), and Japanese (10.5 %) ( Arai et al 2007 ) populations, but lower than Malaysian (20.20 %) ( Wei et al 2015 ), Swedish (20.30 %) ( Eggertsen et al 1993 ), and Norwegians (19.8 %) ( Kumar et al 2002 ) populations.…”
Section: Discussionmentioning
confidence: 67%
“…In contrast, the APOE4 allele showed significantly lower concentrations of TC compared with APOE3 allele in women from Northern Chile ( Gálvez et al 2021 ). Moreover, APOE polymorphism was not found associated with serum lipids in Saudi populations ( Almigbal et al 2018 ). Altogether, we suggested that the different allele frequencies of these polymorphisms among various studies, and the inconsistent results of the association between these polymorphisms, and serum lipids may be due to the different populations, and ethnicities, as well as, the number of the study subjects.…”
Section: Discussionmentioning
confidence: 99%